Marxism and the Leninist Revolutionary Model - Davidshofer, William J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book explores Marxist and Leninist revolutionary theory. Topics include: the philosophical dialectic, historical materialism, the revolutionary movement, and Communist cadre political rule in the socialist state. Emphasis on Lenin's wartime political treatment of imperialism, national self-determination, and socialism in one country.
Keywords: Political science; Political theory; World politics; Political philosophy; Political Science and International Relations; Political Theory; Political Philosophy; Political Science; Political History